Kepusan kerja Karyawan dan Análisis SWOT Dalam Upaya Meningkatkan Manajemen Strategi Pelayanan di RSIGM FKG UMI - Arifin, Nur Fadilah; Wijaya, Muhammad Fajrin; Muslimin, Ulfa Amalia (PT.Mantaya Idea Batara, 2023)
Job satisfaction is factors seen by the organization. If the organization sees satisfaction when employees work, then employees are more active in working so that productivity and service will increase. To find out the strategic design of the hospital, so that the hospital runs with its goals, it needs to do analysis SWOT. SWOT analysis is used to focus on strengths, weaknesses, opportunities, and treats. For job satisfaction and SWOT analysis in an effort to improve service strategy management at RSIGM FKG Universitas Muslim Indonesia (UMI). Researchers used an analytic observational method with a quantitative approach and a cross- sectional research design. Collecting data was carried out using tools, namely questionnaires and SWOT analysis with RSIGM FKG employees’ respondents as many as 35 people. The statistical test used was multiple linear regression. Based on the results of the study there is a significant relationship with employees’ job satisfaction at RSIGM UMI including salary variable value = 0.001, organizational policy value = 0.010, interpersonal relations value = 0.002, responsibility value value = 0.001, working conditions value value = 0.011. Based on the results of the SWOT analysis RSIGM UMI Makassar is in quadrant 1 that able to take advantage of strengths and opportunities, and minimize weaknesses and threats. Based on the results obtained, this shows that there is any influence on employee job satisfaction at RSIGM UMI Makassar and based on the SWOT analysis, RSIGM's position is in quadrant 1.